PERENCANAAN FLEXIBLE PAVEMENT ACCESS ROAD KENDARAAN PKP-PK DI BANDAR UDARA DEPATI PARBO KERINCI - Zahkiyanto Ageng Wicaksono; Bambang Wasito; Setyo Hariyadi (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Depati Parbo Airport is an airport located in Angkasa Pura Village, Sitinjau Laut District, Kerinci Regency, Jambi Province. Having a runway dimension, which is 1800 m long and 30 m wide. The aircraft operating at Depati Parbo Kerinci Airport is ATR 72-600 type. One of the facilities in Depati Parbo Airport Kerinci owned by one of them is Flight Accident Assistance and Fire Department with category V. In planning the Flexible Pavement Acces Road for PKP-PK Vehicles, the data used are PKP-PK vehicle data, rainfall data, CBR value data, and for the method used ks the component analysis method and the method AAHSTO to determain the thinckness of pavement which will later be validated with SKEP 347 of 1999. After getting the results of the calculations that will be used in the planning, the next step is to determine the budget plan using price analysis guidelines issued by the Directorate General of Civil Aviation. From the calculation of the .calculation of component analysis method, the pavement thickness for planning the flexible pavement access road for PKP-PK vehicles is 40 cm where the surface thickness is 5 cm, base course thickness is 15 cm, and the sub base thickness is 20 cm. While the results of the calculation of the method for the surface thickness is 6 cm, base course thickness is 9 cm, and the sub base thickness is 24 cm. Besad on the price of the kerincy regency in 2021 total budged plan required for the PKP-PK vehicle access road is Rp. 1.179.075.000,-.